Agronomic performance of chili hybrids in different types of substrate under protected cultivation (Research, Society and Development, 2020)
Peppers are one of the main fruit vegetables. The aim is to improve the offer of this product, based on increased productivity, making it available at all times of the year and with quality through cultivation in a protected environment. The objective of this work is to evaluate the agronomic performance of two hybrids, yellow and green, grown in three types of substrate. The experiment was carried out in a greenhouse with a 40% chromatinet® screen in the vegetable field of the Department of Technology and Social Sciences at the State University of Bahia. The experimental design adopted was in Randomized Blocks (DBC) in a double factorial scheme in subdivided plots, with three replications and five plants per plot. Variables related to vegetative growth and production components were evaluated. The data were subjected to analysis of variance and comparison between means by Tukey's at 5% probability. The total production (t.ha-1) showed no significant difference between the substrates used. For hybrids, it is noticed that the green hybrid showed a higher productivity value (34.16 t.ha-1) when compared to yellow (25.67 t.ha-1). For fruit length and pulp thickness, there was significant interaction between the hybrids and the substrates used. For the diameter of the fruits, Satrapo presented a larger diameter value compared to the Splendor. For soluble solids and titratable acidity there was no significant interaction between treatments. Although peppers are grown under a protected environment, high temperatures affect the precocity and fruit development of the studied hybrids.